2019
DOI: 10.1155/2019/5014687
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Peroneus Brevis Tendon Tears with Semitendinosus Tendon Autograft

Abstract: Peroneal tendon disorders are common causes of lateral and retromalleolar ankle pain. For irreparable tears of the tendon, a salvage procedure is indicated with segmental resection followed by reconstruction with tenodesis, tendon transfer, or bridging the defect using allograft or autograft. Although there is insufficient evidence to guide which of these treatment options provides the best outcomes, reconstruction with tendon allograft has provided satisfactory clinical results and is effective for pain relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The single-stage grafting with an autograft is preferred because tenodesis is associated with a poorer outcome affecting the biomechanical balance of the foot often resulting in lateral ankle instability [31] . The use of an autograft, gracilis or semitendinosus tendons are usually the preferred choice [7] , [10] , [32] , [33] , [34] . Even though in our case 1 the split of the PB was Grade IV according to Sobel et al classification system [8] , we decided not to proceed in tenodesis as the tendon was healthy and viable without intraoperative subluxation and intact SPR and the final clinical outcome was excellent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single-stage grafting with an autograft is preferred because tenodesis is associated with a poorer outcome affecting the biomechanical balance of the foot often resulting in lateral ankle instability [31] . The use of an autograft, gracilis or semitendinosus tendons are usually the preferred choice [7] , [10] , [32] , [33] , [34] . Even though in our case 1 the split of the PB was Grade IV according to Sobel et al classification system [8] , we decided not to proceed in tenodesis as the tendon was healthy and viable without intraoperative subluxation and intact SPR and the final clinical outcome was excellent.…”
Section: Discussionmentioning
confidence: 99%
“… Author Cases/sex Age Mechanism Diagnosis Treatment Outcome Scheidegger et al [36] M 57 Atraumatic MRI, U/S Open reconstruction of the PB through transfer on the PL Good outcome 3 m post-op Morimoto et al [37] F 40 Injured the ankle while dancing MRI Graft of ipsilateral semitendinosus and gracilis tendons Was able to stand on a single leg in equinus 3 m post-op Jockel et al [38] 4 M, 4 F Mean age 54 Ankle sprain/chronic pain MRI Excellent outcome in 5 pts/eversion weakness in 2 pts/1 pt did not return to preoperative activities and developed the single postoperative complication of a transient peroneal palsy Clement et al [39] F 58 History of recurrent inversion ankle sprains and lateral ankle instability MRI End-to-end implantation of cadaver graft At 2y follow-up had full function without pain or weakness Radice et al [40] M 37 Rupture of the PL and PB tendons secondary to tophaceous gout i MRI PL to PB tenodesis Excellent outcome 1y post-op J Leppilahti et al [41] 2 F Middle age & 53 Car accident/chronic pain U/S Single central PB split was repaired with side-to-side saturation in 1 case. The torn fragment of the PB tendon was excised and the ankle was mobilized early Pts were satisfied, although they still had some exertion pain in their ankle/good outcome Minoyama et al [42] 2 M 17 & 22 Ankle sprain MRI Debridement/the torn tendon was sutured with 4-0 nylon Returned to his full activity 3 m post-op Nishikawa et al [34] 2 M, 1 F Mean age 46 Ankle sprain MRI …”
Section: Discussionmentioning
confidence: 99%
“…Although such studies have illustrated the obvious recovery effect via the conventional open techniques, the perplexing complications that might be related to the large traumatic surgeries were not di cult to notice. In contrast, some researchers demonstrated that patients have a better functional recovery with more mild muscle injuries and low complications via minimally invasive technique [24][25][26][27][28] . However, the clinical outcome of patients with NATR who underwent a minimally invasive surgical approach still needs to evaluate furtherly.…”
Section: Discussionmentioning
confidence: 99%
“…Although the technique for this approach has been described previously, there is limited evidence on outcomes following this procedure. 5,11 This reconstructive method may be more efficacious than repair given that it removes all diseased tissue, which may be the source of pain. The purpose of this study was to evaluate clinical and patientreported functional outcomes for patients who underwent peroneus brevis reconstruction with hamstring autograft.…”
mentioning
confidence: 99%
“…Our goal was to present a larger case series of outcomes following this treatment, as the current literature includes results from only a few patients. 11 We hypothesized that patients would report good functional outcomes and would experience few complications or reoperations.…”
mentioning
confidence: 99%